Expanding choice and access in contraception: an assessment of intrauterine contraception policies in low and middle-income countries - Ali, Moazzam (BMC Public Health, 2019)
BACKGROUND: Globally 214 million women of reproductive age in developing regions have unmet needs in modern contraceptives. Intrauterine contraception (IUC) is highly effective, has few medical contraindications, low discontinuation, and is a low cost modern contraceptive method. However, there is relatively low use of IUDs in LMICs. One reason for this may be policies that restrict IUD availability and use. This study assess national policies pertaining to IUD from a diverse set of countries. METHODS: Between December 2015 and February 2016, a 12-question survey pertaining to IUD policy was sent to WHO regional and country representatives. RESULTS: Sixty-nine surveys were used from countries through WHO regional offices. Among those surveyed, 87% (n = 60) had policies pertaining to IUD use. Among them, 84% (n = 58) reported that hormonal IUDs were available, but only 42% (n = 29) had them in the public sector. Free IUDs in the public sector were available in 75% (n = 52) of countries. For IUD promotion, 75% (n = 52) of countries reported cooperation with NGOs, and 48% (n = 33) received free devices from donors. Policy restrictions beyond the WHO guidelines existed in 15 countries and included restrictions to use for women who were nulliparous, adolescent, unmarried, or had multiple partners. CONCLUSIONS: National policy is important in facilitating modern contraceptive uptake. While many countries who responded in the survey, have policies about IUD use in place, 16% still had none on IUD. Another gap identified was low availability of hormonal IUDs, especially in the public sector. Private sector remains untapped potential in expanding method choice by making IUDs available and accessible in developing countries. Most countries do have policy in place to facilitate IUD use, though there are still gaps in the accessibility of IUDs in many countries. Lastly there is a need to revisit restrictive policies that prevent IUD use for specific populations of women for whom IUDs can be beneficial in realizing their reproductive needs.